Analisis Kinerja Algoritme Speck Pada Keamanan File Teks - Karmila Dewi Sulistyowati; Ari Kusyanti; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
SPECK published by NSA in 2013 as a new block cipher algorithm. This cipher has 10 variations based on block and key sizes, which it has its own characteristics for its encryption and decryption process. This research aimed to analyze the performance of SPECK to secure text file by performing encryption and decryption processes. There were two experiments conducted, first is to analyzed performance of 3 variations of SPECK, such as SPECK128/128, SPECK128/192 and SPECK128/256. These variations was chosen because of previous research that utilized the AES algorithm to secure data where AES has 3 variations based on key lengths, such as AES-128, AES-192 and AES-256. The results obtained from this experiment were the longer the key used, the faster the encryption and decryption process on the system. Second experiment is to analyzed variations of file sizes, such as 50 KB, 100 KB, 150 KB, 200 KB, 250 KB and 300 KB. The results obtained were the larger the file size used will took longer time to process. Afterwards, the results were put in Kruskal-Wallis and Post Hoc tests to be analyzed and concluded with each change of 50 KB in file size will produce a significant time difference.